Amine-borane dehydropolymerization: challenges and opportunities - Colebatch, A; Weller, A (Wiley, 2018)
The dehydropolymerization of amine–boranes, exemplified as H2RB⋅NR′H2, to produce polyaminoboranes (HRBNR′H)n that are inorganic analogues of polyolefins with alternating main‐chain B−N units, is an area with significant potential, stemming from both fundamental (mechanism, catalyst development, main‐group hetero‐cross‐coupling) and technological (new polymeric materials) opportunities. This Concept article outlines recent advances in the field, covering catalyst development and performance, current mechanistic models, and alternative non‐catalytic routes for polymer production. The substrate scope, polymer properties and applications of these exciting materials are also outlined. Challenges and opportunities in the field are suggested, as a way of providing focus for future investigations.